Association of Ishii test scores with pneumonia in stable schizophrenic subjects - Yang, Qin; Huang, Sha; Chen, Ming; Zhu, Tian; Li, Qiuxia; Chen, Xiaoyan (Frontiers in Psychiatry, 2022)
Aim We investigated the relationship between the sarcopenia-indicating Ishii test scores and pneumonia risk in stable schizophrenia patients. Methods This prospective investigation involves schizophrenic inpatients from two mental health centers in western China. Patient baseline information was gathered over 1 month from September 1 to 30 in 2020. All pneumonia-related patient information, including diagnosis and treatment, was acquired over 1 year between October 2020 and October 2021. Patients with schizophrenia were screened for sarcopenia utilizing a threshold value established by Ishii et al. Using regression analysis, the link between Ishii test scores and pneumonia risk in schizophrenia patients was investigated. Result This study recruited 232 males and 107 females with schizophrenia over the age of 50 and older. During a 1-year follow-up period, four patients (3 males and 1 female) acquired pneumonia within 1 week of relapse in schizophrenia; therefore, these patients were excluded from the study. Finally, data were collected for 335 patients. The pneumonia incidences were 29.3% in males and 14.2% in females. Our analysis confirmed that compared to the male schizophrenia patients with Ishii test scores < 105 (non-sarcopenia), those with Ishii test scores ≥ 105 (sarcopenia) exhibited an elevated pneumonia risk (OR = 2.739, 95%CI: 1.406–5.333). Following confounders adjustment, Ishii test scores ≥ 105 remained a risk factor for pneumonia (OR = 2.064, 95%CI: 1.029–4.143). Among females with schizophrenia, the Ishii test scores were not associated with pneumonia risk. Conclusion In conclusion, our results demonstrated that the Ishii test scores ≥ 105 were strongly associated with pneumonia risk in stable schizophrenic male patients.